Digital marketing communication quality and consumer preferences in community-based MSMEs: a correlational survey study - Tia Nurapriyanti; Muhammad Ridha (Indonesian Institute For Counseling, Education and Therapy, 2026)
Digital technology has transformed marketing communication practices, encouraging Micro, Small, and Medium Enterprises (MSMEs) to adopt digital platforms to strengthen consumer engagement. This study analyzes the relationship between digital marketing communication strategies and digital consumer preferences among MSMEs in the Cisadane River area. A quantitative descriptive survey was conducted using closed-ended Likert-scale questionnaires distributed to consumers who had interacted with MSME digital marketing channels through purposive sampling. Data were analyzed using descriptive statistics and correlation analysis. The findings indicate that Instagram and WhatsApp Business are the most frequently used communication platforms, while message clarity, communication consistency, and two-way interaction are the primary factors influencing consumer preferences. Statistical analysis demonstrates a strong positive correlation (r = 0.67) between the quality of digital marketing communication strategies and digital consumer preferences. The results further reveal that communication strategies aligned with local social characteristics enhance consumer engagement and marketing effectiveness. These findings extend the application of integrated marketing communication theory to community-based MSMEs and suggest that effective digital transformation depends not only on technology adoption but also on contextual, consistent, and interactive communication strategies that strengthen the competitiveness of local enterprises.